2017
DOI: 10.1080/13596748.2017.1362534
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress in university students studying in a further education college

Abstract: Orrin (2017) Perceived stress in university students studying in a further education college. Research in Post-Compulsory Education, 22 (3). pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
5
21
0
Order By: Relevance
“…As seen in prior evidence, students with little self-regulation are the ones that require greater external regulation. Certain prior evidence has shown results that concur with this idea ( Shaw et al, 2017 ; Bingen et al, 2019 ). In addition, the teacher’s level of self-regulation ( Capa-Aydin et al, 2009 ) increases the likelihood of regulatory teaching ( Randi, 2004 ; Monshi-Toussi et al, 2011 ), although this relationship has not been addressed in the present study.…”
Section: Discussionmentioning
confidence: 67%
“…As seen in prior evidence, students with little self-regulation are the ones that require greater external regulation. Certain prior evidence has shown results that concur with this idea ( Shaw et al, 2017 ; Bingen et al, 2019 ). In addition, the teacher’s level of self-regulation ( Capa-Aydin et al, 2009 ) increases the likelihood of regulatory teaching ( Randi, 2004 ; Monshi-Toussi et al, 2011 ), although this relationship has not been addressed in the present study.…”
Section: Discussionmentioning
confidence: 67%
“…If the context is non-regulating or dysregulating, it will probably not help students improve their learning process, especially if students have low SR. As seen in prior evidence, students with little SR require greater external regulation. Certain prior evidence has shown results consistent with this idea (Shaw et al, 2017;Bingen et al, 2019;Kassymova et al, 2019).…”
Section: Implications For the Practice Of Educational Psychology At Umentioning
confidence: 60%
“…From an Educational Psychology perspective, however, it seems reasonable to approach the study of stress as a contextualized phenomenon within the teaching-learning process (Mainhard et al, 2018). On one hand, the learning process can by accompanied by the experience of stress and by the use of resources for managing stress (coping strategies), depending on characteristics of the individual (Shaw et al, 2017;Rapillard et al, 2019). On the other hand, the context, or teaching process, can give rise to stressful experiences and to the use of stress management methods (Frenzel et al, 2018;Gentsch et al, 2018;Collie et al, 2019).…”
Section: Academic Stress At Universitymentioning
confidence: 99%
“…Depending on their individual characteristics, students in these contexts use different methods or coping strategies to manage stress [14]. Prior research has reported predictive relationships between self-regulation and coping strategies [15], and between resilience, coping and burnout [16].…”
Section: Introductionmentioning
confidence: 99%